Hubungan Persepsi Siswa tentang Budaya Sekolah dan Motivasi Belajar dengan Penyesuaian Diri Siswa - Fitria, Rini; Marsidin, Sufyarma; Nirwana, Herman (Universitas Negeri Padang, 2014)
The background of research that more than half (52,5%) students were not able to adjust properly. School culture factors, and motivation influence students’ adjustment. The purpose of this research to describe (1) the students’ perception about school culture, (2) learning motivation, (3) students’ adjustment, (4) the correlation students’ perception about school culture with students’ adjustment, (5) the correlation learning motivation with students’ adjustment, and (6) the correlation students’ perception about school culture and learning motivation with students’ adjustment. This research is quantitative method by using descriptive correlational approach. The population are the all students of SMP Negeri 1 Lubuk Alung of Academic Year 2014/2015 (836); amount of research sample is 271 students, and had been chosen by using stratified random sampling technique. The instrument that had been used is questionnaire with reliability as big as 0.860 (students’ perception about school culture), 0.913 (learning motivation), and 0.867 (students’ adjustment). Data analyzed using descriptive statistics, product moment correlation and multiple regression analysis. The results of research are (1) the students’ perception about school culture is in the good category, (2) the students' motivation is in the strong category, (3) the students’ adjusment is in the good category, (4) there is a correlation students’ perception about the school culture with the students’ adjustment (r=0.570, significance 0.000), (5) there is a correlation students’ learning motivation with students’ adjusment (r=0.767, significance 0.000), and (6) there is a correlation between students’ perception about the school culture and learning motivation with the students’ adjusment (R=0.595). The research’s implications to guidance and counseling are used as a input to create a guidance and counseling service programs